PENGARUH PEMBELAJARAN PROBLEM SOLVING VIRTUAL LABORATORY TERHADAP PENGUASAAN KONSEP FISIKA MAHASISWA PADA MATERI AYUNAN PUNTIR - Uranti Amba Lembang; Alfrits Komansilan; Jeferson Polii (Charm Sains: Jurnal Pendidikan Fisika, 2021)
The laboratory becomes medium for learning science that can make students form knowledge and discover physics concepts from the theory that is being studied. However, learning activities in the laboratory generally make students do what they are told in practicum instructions without understanding what they are doing. The purpose of this study was to determine the effect of Problem Solving Virtual Laboratory learning on students' mastery of physics concepts on the Twist Swing material. This study used a quasi-experimental method with a one-group pretest-posttest design. The sample consisted of 18 students of the 2nd semester of the physics education study program. Based on the n-gain test, 15 students were in the high category with 83% and three students in the medium category with 17%. The statistical hypothesis test using the t-test at the significant level = 0.05, the t value is 2.47, and the t table value is 2.11 so that tcount > ttable. From these results, it can be concluded that problem-solving virtual laboratory learning affects students' mastery of physics concepts on torsional pendulum material.